Sulfarotene Inhibits Colorectal Cancer via Mitigating Natural-Killer-Cell-Induced Stemness - Keshu Hu; Yu Dong; Jiayu Zhang; Mengling Liu; Xun Sun; Xin Cao; Pengfei Zhang; Tianshu Liu (MDPI AG, 2024)
Tumor cell stemness stands out as a pivotal factor driving tumor recurrence or metastasis and significantly contributes to the mortality of patients with colorectal cancer (CRC). Recent research has unveiled a link between immune-active cells and the induction of tumor cell stemness, ultimately leading to heightened resistance to treatment. In this study, stemness in CRC cell lines was assessed after co-culture with natural killer (NK) cells, both with and without sulfarotene administration. Furthermore, a CRC xenograft model was utilized to scrutinize the in vivo efficacy of sulfarotene in overcoming stemness induced by NK cell activation. As a result, CRC cells exhibited significant stemness after NK cell co-culture, as evidenced by the upregulation of several stemness markers associated with cancer stem cells. Moreover, these cells demonstrated remarkable resistance to commonly used chemotherapy agents for CRC, such as oxaliplatin and irinotecan. Importantly, sulfarotene effectively reversed the altered stemness of CRC cells in both in vitro and in vivo assays. In conclusion, sulfarotene emerges as a promising therapeutic strategy for overcoming colorectal cancer resistance to NK cells by effectively inhibiting stemness remodeling. This study underscores the potential of sulfarotene in augmenting NK-cell-mediated immune surveillance, proposing a novel immunotherapeutic approach against colorectal cancer.